10 - {10 - [10 - (10-2 x X)]} : 10 = 10
Multumesc anticipat!
Răspunsuri la întrebare
Răspuns de
2
10 - {10- [10-(10-2 x X)]}= 100
10-[10(10-2 x X)]= 110
10( 10-2 x X) =120
10-2x X=12
2X=22
X=11
10-[10(10-2 x X)]= 110
10( 10-2 x X) =120
10-2x X=12
2X=22
X=11
mikewaz:
Multumesc din suflet!
Răspuns de
2
10-{10-[10-(10-2x)]}=100
10-10+10-2x=90
90-10+10-10=2x
2x=80
x=80/2
x=40
10-10+10-2x=90
90-10+10-10=2x
2x=80
x=80/2
x=40
Alte întrebări interesante
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Chimie,
10 ani în urmă
Ed. tehnologică,
10 ani în urmă